PENGARUH KOMBINASI NUTRISI AB MIX DAN PUPUK GANDASIL D TERHADAP PERTUMBUHAN DAN HASIL PEPPERMINT SECARA HIDROPONIK - SAPUTRA, JOKO; ASTINA, ASTINA; HARIYANTI, AGUS (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the effect of the combination of AB-Mix nutrition and Gandasil D fertilizer on the growth and yield of peppermint in hydroponics and obtain the best concentration of a combination of AB-Mix nutrition and Gandasil D fertilizer on the growth and yield of peppermint hydroponically. This research was conducted in Roban Village, Singkawang Tengah District, Singkawang City. It was starting from April 21, 2018 to June 8, 2018. This study used a Completely Randomized Design (CRD), which consisted of 6 treatments and 4 replications of each treatment consisting of 3 samples, so that there were 72 plants. The treatment in question is, a1: AB-Mix 75% + Gandasil D 2 g / l, a2: AB-Mix 75% + Gandasil D 4 g / l, a3: AB-Mix 75% + Gandasil D 6 g / l, a4: AB-Mix 50% + Gandasil D 4 g / l, a5: AB-Mix 50% + Gandasil D 6 g / l, a6: AB-Mix 50% + Gandasil D 8 g / l. Observation variables included the root volume (cm3), plant height (cm), number of leaves (strands), leaf chlorophyll (spad unit), fresh weight of the upper part of the plant (g), dry weight of the upper part of the plant (g). The results showed that the combination of AB-Mix nutrition and Gandasil D fertilizer could increase the growth and yield of peppermint hydroponically on the variable root volume, number of leaves, fresh weight of the upper part of the plant, top dry weight of plants and combination treatment of nutrients AB-Mix 75% + Gandasil D 2 g / l is an efficient dose to produce fresh weight in the upper part of the peppermint plant hydroponically. Keywords: Hydroponics, Gandasil D, AB-Mix Nutrition, Peppermint.